Role of lectins as biologically active substances in pharmaceutical preparations - V. A. Antonyuk (LLC "Publisher OKI", 2014)
In an overview and critical article discusses plant lectins in terms of their importance as biologically active substances in pharmaceutical preparations. Focuses on the critical analysis of the possible values of lectins medicinal plants in pharmaceuticals and analysis of the most common errors scientific papers on the subject. The analysis of some pharmaceuticals, in which the main active ingredients are declared lectins.